Report of the Study Group on Financing of the Private Corporate Sector in the Sixth Five Year Plan - Planning Commission (Planning Commission, 1982)
The private corporate sector has been accorded, an important and complementary role to the public sector in the Sixth Five Year Plan in the attainment of the Plan targets. Consistent with the capacity and production targets envisaged for various industries in the Plan, it has been indicated in the Plan document that the private corporate investment in mining and manufacturing would be Rs. 13,182 crores and that in addition an investment of Rs. 4,400 crores would be made in the non-financial services sector, thus making a total of Rs. 17,582 crores.
Government of India Planning Commission
Government of India Planning Commission